Reduction of ground-borne vibrations from rail lines on viaducts by means of elastic anti-vibration mats. (May 2019) - Zhao, Caiyou; Ping, Wang; Xing, Mengting; Yi, Qiang; Wang, Liuchong
In this paper, the effectiveness of elastic anti-vibration mats in reducing ground-borne vibrations from rail viaducts is investigated by means of theoretical analysis and is validated by the results of field tests. A two-step procedure is adopted for analyzing the vehicle-track-bridge-soil coupling system. In the first step, the train-track-bridge-pier subsystem is considered, and the bridge-bearing reaction force is solved. In the second step, the pier-pile-soil subsystem is considered, and the ground vibration solution is obtained by applying the negative bridge-bearing reaction force to the pier top on a pier-pile-soil model. The accuracy of the presented model is then verified in comparison with in-situ measurement results. On the basis of this comparison, a parametric study on the impact of anti-vibration mats on ground-borne vibrations was investigated theoretically, and the effectiveness of elastic anti-vibration mats with the suggested optimal parameters was further validated by field tests. The results show that when the stiffness of the elastic anti-vibration mats is 1.5 MPa/m, ground vibration decreases significantly and the vertical rail displacement agrees with high-speed railway regulations.